Pengembangan Aplikasi Augmented Reality Sebagai Media Pembelajaran Perakitan dan Instalasi Mesin: English - Ardhiyanto, Firmansah Dwi; Tuwoso, Tuwoso; Widiyanti, Widiyanti; Marsono, Marsono (BRILIANT: Jurnal Riset dan Konseptual, 2025)
There are several courses at the State University of Malang, Faculty of Engineering, Mechanical Engineering Department, one of which is Machine Assembly and Installation which studies knowledge related to management, procedures and materials used to assemble and install machines. The learning process is not optimal because there is no demonstration of the use of lifting aircraft due to limited availability. Therefore, learning media innovations are needed that aim to contain comprehensive material and visualizations lifting aircraft in 3D. Digital AR learning media that is easy to operate by students flexibly. Developing augmented reality-based learning media on lifting aircraft for engine assembly and installation courses and testing its feasibility are the objectives of this study. This development uses the ADDIE model. The results of this study are as follows: (1) material validation obtained a percentage value of 94.31%, which is classified as very feasible; (2) media expert validation showed the feasibility level with a percentage of 93.75%; and (3) the results of small group trials showed a very feasible level with a percentage of 90.12%. The implication of this research is to increase learning effectiveness, increase student learning motivation and facilitate teaching lecturers in the knowledge transfer process.